Central Nervous System Tumors Primary and Secondary - Birol Sarica, Feyzi (IntechOpen, 2023)
Central nervous system (CNS) tumors are a heterogeneous group consisting of more than 100 tumor types originating from the brain, cerebellum, brain stem, spinal cord, and meninges. Despite the positive developments of recent years, especially in the treatment of high-grade brain tumors, treatment outcomes have not yet reached an acceptable level. However, due to advances in clinical and experimental studies, the genetic and molecular structures of many high-grade CNS tumors are now better understood. The World Health Organization's 2021 Classification of CNS Tumors has aided the understanding of the genetic, molecular and immunological structures of these tumors as well as their interactions with their microenvironment. Targeted therapies and vaccines developed with immunotherapy protocols are promising developments. This book explores the natural history of CNS tumors and discusses relevant treatment protocols.